2014
DOI: 10.1387/ijdb.140096sr
|View full text |Cite
|
Sign up to set email alerts
|

Immunological determinants of implantation success

Abstract: The capacity of the immune system to maintain the integrity of the individual requires recognition and control of entities identified as genetically distinct, or 'non-self' . In mammalian reproduction, the embryo and subsequent fetus and placenta are all recognized as non-self by the maternal immune system, and are vulnerable to immunological attack. An active system to prevent rejection must exist from when conceptus and maternal tissues first come into contact at implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 159 publications
0
96
0
1
Order By: Relevance
“…Proper establishment, progress and success of mammalian pregnancy rely on the capability of the maternal immune system to undergo a series of adaptations tending to tolerate the presence of the semi-allogeneic fetus (Robertson and Moldenhauer, 2014;Seavey and Mosmann, 2008). Among others well described immune-mechanisms; our laboratory has demonstrated that pregnancy induces strong modifications in B cell development (Muzzio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Proper establishment, progress and success of mammalian pregnancy rely on the capability of the maternal immune system to undergo a series of adaptations tending to tolerate the presence of the semi-allogeneic fetus (Robertson and Moldenhauer, 2014;Seavey and Mosmann, 2008). Among others well described immune-mechanisms; our laboratory has demonstrated that pregnancy induces strong modifications in B cell development (Muzzio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the programmed cell death ligand (PDL1) is crucial for maternal tolerance in allogeneic pregnancies (2). Finally, the presence of regulatory T cells (Tregs) is instrumental to the maintenance of maternal tolerance (3), where fetus-specific Tregs remain after pregnancy (4) and can expand in subsequent pregnancies (5). Immune tolerance of the fetus relies on the concerted actions of hormones and cytokines, as well as cross-talk between innate and adaptive immune cells (6).…”
mentioning
confidence: 99%
“…It is assumed that in the decidua, the Tregs mainly fulfill immunosuppressive action [16]. Treg lymphocytes have anti-inflammatory and immunosuppressive effects [96], secrete IL-10, TGF-β, IL-4, IL-5 [32], express GATA3 ( Figure 1, Table 1) [29]. Treg lymphocytes inhibit proliferation and production of cytokines by T cells, production of immunoglobulins by B-cells, cytotoxic activity of NK-cells, DC maturation, and, thus, contribute to tolerance formation [104].…”
Section: Cd11bmentioning
confidence: 99%
“…Treg Тh3 subpopulation is characterized by TGF-β and IL-10 secretion and FoxP3 expression [87]. CD4 + CD25 -alteration into Treg cells at the periphery (outside the thymus) occurs with obligatory B7 molecule co-stimulation [61], at activation through TcR [35] in cooperation with action of IL-10 and TGF-β cytokines [42,109,121], the source of which is the trophoblast in the zone of the uteroplacental bed [17,29,96,120]. Estradiol promotes Treg differentiation and increases their proliferation in response to activation through CD3/CD28 [131].…”
Section: Cd25mentioning
confidence: 99%
See 1 more Smart Citation